Validity of the Liebowitz Social Anxiety Scale (LSAS) Measurement Tool - Kalalo, Beatrice; Marlietama, Celine Amanda; Cristabel, Graceveline (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
Social phobia is a person's fear when they are doing something in front of others, such as eating, drinking, shaking, blushing, talking, writing or vomiting. This activity refers to anxiety in a person. There are two aspects to identify anxiety, performance and social. This study aims to test the validation of the Liebowitz Social Anxiety Scale (LSAS) measurement tool. This research is a quantitative study that involved active undergraduate students as subjects aged 17-25 years. The subjects were 177 students from various institutions in Indonesia. Data is obtained through google forms that are shared online and the data is processed using the SPSS application. Accidental sampling was used for this study, so the subjects needed were subjects who met the above criteria. Validation of the measurement tool uses evidence sources based on internal structures and correlations with other measuring instruments (Beck Depression Inventory and Social Interaction Anxiety Scales). The results obtained from this study prove that the LSAS measuring instrument is valid and can be used to measure social anxiety.